Lipidoid-siRNA Nanoparticle-Mediated IL-1β Gene Silencing for Systemic Arthritis Therapy in a Mouse Model - Song, Ping (Mol Ther, 2019)
Interleukin-1 beta (IL-1β) plays a central role in the induction of rheumatoid arthritis (RA). In the present study, we demonstrated that lipidoid-polymer hybrid nanoparticle (FS14-NP) can efficiently deliver siRNA against IL-1β (siIL-1β) to macrophages and effectively suppress the pathogenesis of experimental arthritis induced by collagen antibody (CAIA mice). FS14-NP/siIL-1β achieved approximately 70% and 90% gene-silencing efficiency in the RAW 264.7 cell line and intraperitoneal macrophages, respectively. Intravenous administration of FS14-NP/siRNA led to rapid accumulation of siRNA in macrophages within the arthritic joints. Furthermore, FS14-NP/siIL-1β treatment lowered the expression of pro-inflammatory cytokines in arthritic joints and dramatically attenuated ankle swelling, bone erosion, and cartilage destruction. These results demonstrate that FS14-NP/siIL-1β may represent an effective therapy for systemic arthritis and other inflammatory disorders.